If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 66 + -3t = 5(t + 102) Reorder the terms: 66 + -3t = 5(102 + t) 66 + -3t = (102 * 5 + t * 5) 66 + -3t = (510 + 5t) Solving 66 + -3t = 510 + 5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-5t' to each side of the equation. 66 + -3t + -5t = 510 + 5t + -5t Combine like terms: -3t + -5t = -8t 66 + -8t = 510 + 5t + -5t Combine like terms: 5t + -5t = 0 66 + -8t = 510 + 0 66 + -8t = 510 Add '-66' to each side of the equation. 66 + -66 + -8t = 510 + -66 Combine like terms: 66 + -66 = 0 0 + -8t = 510 + -66 -8t = 510 + -66 Combine like terms: 510 + -66 = 444 -8t = 444 Divide each side by '-8'. t = -55.5 Simplifying t = -55.5
| 9x+8=-91 | | 2x-4=4(x-3) | | k/-14=0 | | -1/5-3/5 | | 1/7x+2/3x=1 | | 1+7p=3p-11 | | 2-x=7x-54 | | 1=-c^2 | | a-b-(a+b)=0 | | 7x^2=103 | | -1=11 | | 4x(5-x)= | | -14-16.5a=-3(6a+4) | | (4x-5)2=49 | | 5/8-11/20 | | (372+x)+x+(x-73)=3063 | | -3n-n=-20 | | 10(y+2)=-2(2y+3) | | 6=-5/8+u | | -8x-x=0 | | 3.4+10x=7.81 | | -4-14y=-3y+2(-3y/2-1) | | 17x^2-17x+34=0 | | (4x+10)=(3x+10) | | v-1/4=-3/8 | | 2x+4x-2=20 | | (8+v)(3v+7)=0 | | 2(k+3)=7-3k | | 3p-4=-6 | | -2=-b-6 | | 2*(0.5x-4)=-(x-5) | | 3x/7+8/7=1 |